Difficulties and possible mistakes in applying AI techniques in industrial control systems by new generation of engineers. - Raducan, Elena; Arhip, Mihaita; Guzu, Sorin (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Nowadays, Artificial Intelligence (AI) is making its entrance in absolutely all fields and only the economic level of the promoting states is responsible for the percentage of the insertion of this new technology. The economic aspect is not directly connected with the AI because there is already a wide range of open-source software’s and AI analysis models but is strictly connected with the digitalization level of the country and/or company that wants to follow this trend. This article proposes a subjective analysis of some situation that young engineers can face by early use of dedicated software’s for data analysis rise from different systems.